On trans becoming: an interpretive phenomenological analysis of trans higher education staff - Vigil, Rye B., author; Muñoz, Susana, advisor; Lange, Alex, committee member; Rivera, Carmen, committee member; Hentschell, Roze, committee member (Colorado State University. Libraries, 2025)
The study explores the fluid and nonlinear process of trans becoming among transgender staff in higher education, challenging traditional narratives of linear gender transition. Using interpretive phenomenological analysis (IPA) and Queer Phenomenology, the study centers on the experiences of trans employees who begin a gender transition while working at the same institution they previously identified as a different gender, navigating environments shaped by cisnormativity and heterosexism. Key themes include the emotional and physical labor of workplace transitions, trans taxation, institutional negligence, and moments of trans joy. Participants describe the tension between visibility and (in)visibility and renegotiating gendered interactions with colleagues. The findings highlight the significant challenges trans employees face due to a lack of institutional support and a disconnect between purported values of growth and support for employees to embody such growth in personal identity. Filling a gap in the literature on transgender employees in higher education, the study offers insights into systemic barriers and institutional shortcomings. Recommendations include policy reform, improved workplace practices, and sustained support systems, especially in the context of rising anti-trans legislation and hostility in the U.S.
Keywords: phenomenology; queer phenomenology; transgender; queer; higher education; trans